Flowers and Value of Conservation in The Culture of Hindu Community in Bali - Darma, I Dewa Putu; Sutomo, Sutomo; Hanum, Siti Fatimah; Iryadi, Rajif; Rahayu, Ayyu (Biosaintifika: Journal of Biology & Biology Education, 2021)
Balinese Hindu community cannot be separated from plant in their life. The information on plant species and how to utilize them are easy to find but limited information about the potency of flowers in the Balinese Hindu community. Flowers have a meaning as sincerity, a symbol of Sang Hyang Widhi, the valour, and also have mythological values. This research aimed to determine the species of flowering plants that are often used for ceremonial and understand the meaning, the cultural conception related to conservation education. The study was carried out in four locations in Tabanan Regency (Baturiti, Penebel, Marga, and Tabanan). Data were collected using an interview with purposive sampling. Data analysis based on the value of Relative Frequency (FR) which is indicated plant most widely used. Â A total of 36 species of flowers are used in traditional Hindu religious ceremonies, of which 29 species are cultivated plants and 7 species are still wild. There are ten of plants which have high FR value, such as: Cananga odorata (FR 0.069), Impatiens balsamina (FR 0.069), Hydrangea macrophylla (FR 0.069), Plumeria acuminata (FR 0.069), Tagetes erecta (FR 0.069), Magnolia champaca (FR 0.069), Gomphrena globosa / bunga ratna (FR 0.047), Gardenia jasminoides / jempiring (FR 0.039), Nymphaea spp./ tunjung (FR 0.030), and Hibiscus rosa-sinensis L./ pucuk (FR 0.030). This research revealed the role of flower in Hindu ceremony and describe the strategic plant conservation due to culture of Balinese Hindu community. Finally, this research expected to documented local knowledge about flowers used as Hindu religious ceremonies, to provide an understanding of the meaning and conceptions of culture related to conservation education.